Central giant cell granuloma of maxillary bone: A case report - Mohammadi, Maryam; Shahabinejad, Mehdi; Mohtasham, Nooshin; Tehran, Farnaz M. (Hasanuddin University, 2022)
Central Giant Cell Granuloma (CGCG) is a benign, intraosseous osteolytic lesion which often affects the mandible and its’ pathophysiology is not fully understood. Histopathology is still the dominant diagnostic method for this disorder. Clinically invasive lesions can lead to premature injury and may require invasive treatment to prevent recurrence. In this study, a case of invasive CGCG of maxillary bone in a 9-year-old boy with diagnostic and therapeutic challenges was presented.